Dolly Parton - Skwish, Emily; e rtist (Chicago, Illinois : Sunbird Books, 2022)
A graphic novel biography of country singer Dolly Parton.
3.9
3-6
GN710L
Keywords: Parton, Dolly -- Comic books, strips, etc; Country musicians -- Biography -- Comic books, strips, etc; Country musicians -- Biography -- Juvenile literature; Parton, Dolly -- Cartoons and comics; Country musicians -- Cartoons and comics; Women -- Biography -- Cartoons and comics; Biographical comics; Nonfiction comics; Comics (Graphic works); Biographies; Graphic novels